Erdosteine prevents colonic inflammation through its antioxidant and free radical scavenging activities - AKSOY, HALİL; ÇETİNEL, ŞULE (SPRINGER, 2007)
After intracolonic administration of trinitrobenzene sulphonic acid (TNBS), Sprague-Dawley rats were treated orally either with saline or erdosteine (100 mg/kg per day), a sulfhydryl-containing antioxidant, for 3 days. On the 4th day, rats were decapitated and distal colon was removed for the macroscopic and microscopic damage scoring, for the measurement of malondialdehyde (MDA), glutathione (GSH) and collagen levels, myeloperoxidase (MPO) activity, luminol and lucigenin chemiluminescences (CL) and DNA fragmentation. Lactate dehydrogenase (LDH) activity, tumor necrosis factor-alpha, interleukin (IL)-1 beta, IL-6, and antioxidant capacity were assayed in blood samples. Colitis caused significant increases in the colonic CL values, macroscopic and microscopic damage scores, MDA and collagen levels, MPO activity and DNA fragmentation, along with a significant decrease in tissue GSH level. Similarly, serum cytokines and LDH were elevated in the saline-treated colitis group as compared with the control group. On the other hand, erdosteine treatment reversed all these biochemical indices, and histopathologic alterations induced by TNBS, suggesting that erdosteine protects the colonic tissue via its radical scavenging and antioxidant activities.
Keywords: erdosteine; colitis; oxidative damage; inflammation; TNBS; TRINITROBENZENE SULFONIC-ACID; SH-METABOLITE-I; INDUCED COLITIS; BOWEL-DISEASE; ULCERATIVE-COLITIS; RESPIRATORY BURST; N-ACETYLCYSTEINE; MUCOSAL DAMAGE; NITRIC-OXIDE; DNA-DAMAGE